Running in good faith? : observant Judaism and libertarian politics - Krinsky, Alan D. (Cherry Orchard Books, an imprint of Academic Studies Press, 2020)
Considers the seemingly irreconcilable values and political commitments of Judaism and Libertarianism, stimulating a broad discussion and calling into question what people think they know about both Judaism and Libertarianism.